A panoramic account of Ibn Batuta’s voyage to maritime Southeast Asia - Arshad Islam, Islam (2018)
The legendary medieval Muslim traveller, Ibn Batuta (1304-1368), was the author of one of the most celebrated travelogues, his Rehlah (Travels). He travelled across most of the Muslim world, from his home in Tangier to China and Southeast Asia, covering some 75,000 miles. After staying many years in Delhi he was finally deputed on a diplomatic mission to China. On his way he traversed Malabar, the Maldives, Sri Lanka, Coromandel, Bengal and Assam. Facing the fury of the Indian Ocean, he sailed to Sumatra on his final mission to China. This paper highlights Ibn Batuta’s voyage to the Indo-Malay Archipelago as a centre of the spice trade and a nexus for merchants of global trade between China, India, Persia, and Southern Arabia with much wider cultural impacts – as evidenced by the presence of Ibn Batuta himself. His insights into the society of medieval Southeast Asia from the perspective of an educated traveller from one of the most sophisticated and distant parts of the Arab-Islamic world offer many important insights on the development of Nusantara society.